РОЛЬ miR26b5p ТА miR1865p У ХВОРИХ НА РАК МОЛОЧНОЇ ЗАЛОЗИ МОЛОДОГО ВІКУ: КЛІНІЧНІ АСОЦІАЦІЇ ТА ВПЛИВ НА ВІДПОВІДЬ НА АНТРАЦИКЛІНВМІСНУ ТЕРАПІЮ - Martyniuk, О.; Mushii, O.; Chekhun, V. (PH Akademperiodyka, 2026)
Background. Age-specific biological differences in breast cancer (BC) shape the disease course, therapeutic sensitivity, and prognosis. The microRNAs hsa-miR-26b-5p and hsa-miR-186-5p are considered promising biomarkers of tumor aggressiveness and treatment response, yet their age-dependent expression features remain insufficiently characterized. Aim. To evaluate age-related expression patterns of hsa-miR-26b-5p and hsa-miR-186-5p in the BC tissue samples and their relation to the response to neoadjuvant 4AC chemotherapy. Materials and Methods. Expression levels of hsa-miR- 26b-5p and hsa-miR-186-5p were analyzed by qRT-PCR in formalin-fixed paraffin-embedded tissue samples of BC patients (n = 56) divided into two age groups: ≤45 and >45 years. MiRNAs expression patterns were analyzed in relation to molecular BC subtype, disease stage, T and N categories by TNM, and treatment response grades assessed by the Miller — Payne system. Results. Patients ≤45 years exhibited significantly higher miR-26b-5p levels (1.78-fold; p = 0.0005), especially in the luminal B subtype tumors (7.26—8.45-fold). The reduced miR-26b-5p and miR-186-5p levels in younger patients were associated with a locoregionally advanced disease (stage III) and lymph-node metastasis. In patients ≥45 years, miR-186-5p levels were significantly higher in the HER2/neu-positive subtype (2.9-fold; p = 0.0278) and in the younger patients responding to 4AC NACT compared to the older responders. Conclusions. In BC, hsa-miR-26b-5p and hsa-miR-186-5p exhibited pronounced age-specific regulatory patterns and could be considered potential markers of BC course and efficacy of anthracycline-based therapy.